تطوير نظم المعلومات المحاسبية باستخدام أدوات تكنولوجيا المعلومات بين الخصائص والمعوقات والمخاطر - أمينة محمد سالم علي (Aljameai, 1970)
Abstract :This Study Aimed To Identify The Characteristics, Obstacles And Risks Of Using Information Technology Tools To Develop Accounting Information Systems, And In Order To Reach The Goals Of The Study Using The Researcher Descriptive Analytical Method Of The Aspects Of The Study, Through Research And Access To The Literature Of The Subject Of The Study.The Study Concluded That Although There Are Several Characteristics For Using Information Technology Tools To Develop Accounting Information Systems; However, There Are Several Times That Prevent The Development Of These Systems In Economic Units, Which Can Result In Some Risks